Jmjd3/IRF4 axis aggravates myeloid fibroblast activation and m2 macrophage to myofibroblast transition in renal fibrosis - Liang, Hua; Liu, Benquan; Gao, Ying; Nie, Jiayi; Feng, Shuyun; Yu, Wenqiang; Wen, Shihong; Su, Xi (Frontiers in Immunology, 2022)
Renal fibrosis commonly occurs in the process of chronic kidney diseases. Here, we explored the role of Jumonji domain containing 3 (Jmjd3)/interferon regulatory factor 4 (IRF4) axis in activation of myeloid fibroblasts and transition of M2 macrophages into myofibroblasts transition (M2MMT) in kidney fibrosis. In mice, Jmjd3 and IRF4 were highly induced in interstitial cells of kidneys with folic acid or obstructive injury. Jmjd3 deletion in myeloid cells or Jmjd3 inhibitor reduced the levels of IRF4 in injured kidneys. Myeloid Jmjd3 depletion impaired bone marrow-derived fibroblasts activation and M2MMT in folic acid or obstructive nephropathy, resulting in reduction of extracellular matrix (ECM) proteins expression, myofibroblasts formation and renal fibrosis progression. Pharmacological inhibition of Jmjd3 also prevented myeloid fibroblasts activation, M2MMT, and kidney fibrosis development in folic acid nephropathy. Furthermore, IRF4 disruption inhibited myeloid myofibroblasts accumulation, M2MMT, ECM proteins accumulation, and showed milder fibrotic response in obstructed kidneys. Bone marrow transplantation experiment showed that wild-type mice received IRF4-/- bone marrow cells presented less myeloid fibroblasts activation in injured kidneys and exhibited much less kidney fibrosis after unilateral ureteral obstruction. Myeloid Jmjd3 deletion or Jmjd3 inhibitor attenuated expressions of IRF4, α-smooth muscle actin and fibronectin and impeded M2MMT in cultured monocytes exposed to IL-4. Conversely, overexpression IRF4 abrogated the effect of myeloid Jmjd3 deletion on M2MMT. Thus, Jmjd3/IRF4 signaling has a crucial role in myeloid fibroblasts activation, M2 macrophages to myofibroblasts transition, extracellular matrix protein deposition, and kidney fibrosis progression.